2007
DOI: 10.14411/eje.2007.064
|View full text |Cite
|
Sign up to set email alerts
|

The association between wing morphology and dispersal is sex-specific in the glanville fritillary butterfly Melitaea cinxia (Lepidoptera: Nymphalidae)

Abstract: Abstract. We examined whether dispersal was associated with body and wing morphology and individual quality, and whether such an association was sex-specific, in the Glanville fritillary butterfly Melitaea cinxia (L.) in Paldiski on the north coast of Estonia. Body weight, size and shape of both fore-and hindwing, wing aspect ratio and wing loading were used as measures of body and wing morphology. Fluctuating asymmetry (FA) of wing shape was used as a measure of individual quality. Males and females did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 62 publications
2
55
1
Order By: Relevance
“…Asymmetry of the wing, tail and tarsus did not affect orientation during migration in three European birds (Sylvia atricapilla, Phoenicurus phoenicurus, Erithacus rubecula) (Matessi 1997). Likewise, the FA of wing shape did not differentiate between dispersal rates in a butterfly (Melitaea cinxia) from the north coast of Estonia (Breuker et al 2007). Our results suggest that the information incorporated into the otolith shape is in some way related (either directly or indirectly through other variables) to the strength of replenishment pulses.…”
Section: Discussionmentioning
confidence: 83%
“…Asymmetry of the wing, tail and tarsus did not affect orientation during migration in three European birds (Sylvia atricapilla, Phoenicurus phoenicurus, Erithacus rubecula) (Matessi 1997). Likewise, the FA of wing shape did not differentiate between dispersal rates in a butterfly (Melitaea cinxia) from the north coast of Estonia (Breuker et al 2007). Our results suggest that the information incorporated into the otolith shape is in some way related (either directly or indirectly through other variables) to the strength of replenishment pulses.…”
Section: Discussionmentioning
confidence: 83%
“…Although they have intersecting areas, each of them had a significantly different wing shape. There are many processes which could explain the fact that all males had a straight wing marginal border while females had a concave border (Dudley 2000;Breuker et al 2007a). These variations may be explained by the flight characteristics of lepidopterans.…”
Section: Discussionmentioning
confidence: 99%
“…Wing loading as measured by weight to wing span has been shown to affect dispersal in insects such as butterflies and damselflies. [28][29][30][31] In Drosophila, there is evidence for an association between wing loading and resource finding ability that contributes to an antagonistic interaction between wing size and thorax length. 32 An association between wing shape and fitness has also been suggested in insects including parasitoids (e.g., Reference 10), although some researchers have suggested that shape may be phenotypically invariable and unlikely to affect fitness.…”
Section: Introductionmentioning
confidence: 99%